Computed Tomographic Evaluation of Adjacent Segment Motion after Ex Vivo Fusion of Equine Third and Fourth Cervical Vertebrae - Schulze, Nicole; Ehrle, Anna; Weller, Renate; Fritsch, Guido; Gernhardt, Jennifer; Ben Romdhane, Recem; Lischer, Christoph (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective Surgical fusion of vertebral segments is a treatment option for horses with cervical stenotic myelopathy or cervical fracture.Degenerative disease affecting adjacent vertebral segments is a reported complication following surgical vertebral fusion in other species, termed adjacent segment disease. The aim of this study was to evaluate the impact of cervical vertebral fusion on the biomechanics of adjacent vertebral segments in the horse.Study Design Neck specimens of 12 horses were assessed using computed tomographic imaging. Range of motion (ROM) was determined by measuring the maximum sagittal flexion, extension and lateral bending between C2 and C5. C3/4 was subsequently fused using a standard locking compression plate and locking head screws and computed tomographic scans and ROM measurements were repeated.Results Prior to intervertebral fusion, a significant increase in ROM along the vertebral segments from cranial to caudal was observed. Range of motion measurements of C3/4 decreased significantly after fusion (p = 0.01).Range of motion of the adjacent segments (C2/3 and C4/5) did not change significantly after fusion.Conclusion Fusion of one cervical intervertebral joint did not affect the ROM of the adjacent vertebral segments. Further research investigating the implications of vertebral fusion on the intervertebral pressure in the equine patient is indicated.
Keywords: cervical fusion; spine fusion; adjacent segment disease; range of motion; equine; equine cervical vertebrae